Листи із сорок першого (фронтові трикутники опішненського гончаря Івана Сердюка до своєї сім’ї) - Міщанин, В. (Сiверянський лiтопис, 2016)
У статті подано короткі біографічні дані про опішненського гончаря Івана Сердюка
та його братів-гончарів Петра й Василя. Наведені мовою оригіналу сім листів червоноармійця Івана Сердюка до своєї сім’ї, написані ним за тиждень до початку німецько-радянської війни та в перші її два місяці. В статье подаются краткие биографические данные опошнянского гончаря Ивана
Сердюка и его родных братьев-гончаров Петра и Василия. Приведены на языке оригинала
семь писем красноармейца Ивана Сердюка к своей семье, написанные им за неделю до
начала немецко-советской войны и в первые её два месяца. Ivan Serdyuk was born in 1909 in the town of Opishne in the Opishne volost of the Zinkiv
District of the Poltava Government (now the Opishne village council of the Zinkiv District of
the Poltava Region) in the Serhiy and Olena Serdyuks’ pottery family. Until his marriage, he
lived and made pots together with his father. In the 1930s, he worked as a potter in the Opishne
co-operative association Art Ceramist. His two brothers, Petro and Vasyl, were potters too.
In the early 1930s, Ivan Serdyuk served in the Workers’ and Peasants’ Red Army (RKKA).
After the military service, he had to attend a retraining in the village of Yaresky every year. He
was a participant in the «liberation» campaigns of the Red Army into Western Ukraine (1939)
and Baltic States: Estonia, Latvia, Lithuania (1940), took part in the Winter War.
In May 1941, he was again called out for muster into the village of Yaresky for 45 days. The
Soviet-German War began on 22 June 1941, and Ivan was not seen at home anymore. Seven
letters written by him a week before the war, on the second day of the war, on the way into the
hospital after the injury, and from the hospital remained as a memory for his relatives about
their husband and father for decades. Now they are kept in the National Archives of Ukrainian
Pottery of the National Museum of Ukrainian Pottery in Opishne.
After the long medical treatment, Ivan Serdyuk was again sent to the front where he fell in
battle. But the exact date and place of his death are unknown to this day.